Melatonin Has the Potential to Alleviate Cinnamic Acid Stress in Cucumber Seedlings - Li, Juanqi; Li, Yang; Tian, Yongqiang; Qu, Mei; Zhang, Wenna; Gao, Lihong (Frontiers in Plant Science, 2017)
Cinnamic acid (CA), which is a well-known major autotoxin secreted by the roots in cucumber continuous cropping, has been proven to exhibit inhibitory regulation of plant morphogenesis and development. Melatonin (MT) has been recently demonstrated to play important roles in alleviating plant abiotic stresses. To investigate whether MT supplementation could improve cucumber seedling growth under CA stress, we treated cucumber seeds and seedlings with/without MT under CA- or non-stress conditions, and then tested their effects on cucumber seedling growth, morphology, nutrient element content and plant hormone. Overall, 10 μM MT best rescued cucumber seedling growth under 0.4 mM CA stress. MT was found to alleviate CA-stressed seedling growth by increasing the growth rates of cotyledons and leaves and by stimulating lateral root growth. Additionally, MT increased the allocation of newly gained dry weight in roots and improved the tolerance of cucumber seedlings to CA stress by altering the nutrient elements and hormone contents of the whole plant. These results strongly suggest that the application of MT can effectively improve cucumber seedling tolerance to CA stress through the perception and integration of morphology, nutrient element content and plant hormone signaling crosstalk.